ANALISIS FAKTOR-FAKTOR DALAM PENGAMBILAN KEPUTUSAN NASABAH MEMILIH PRODUK PEMBIAYAAN PENSIUN DI BSM KC BOJONEGORO SUMBERREJO - rachman, aditya; Swadjaja, Isma (Universitas Muhammadiyah Surabaya, 2020)
Pension financing is a solution for someone who has stopped working to be able to meet all consumptive needs and other economic needs. PT Bank Syariah Mandiri Branch Office Bojonegoro Sumberrejo is one of the Sharia banks that offers pension financing products so that they have to compete with neighboring banks, especially conventional banks, which first offer pension financing products. The population in this study were all retired customers of PT Bank Syariah Mandiri Branch Office Bojonegoro Sumberrejo, as many as 480 customers. By using purposive sampling technique, the number of samples used is 267 retired customers who have met the criteria determined by the researcher. From the analysis, it is found that partially the factors that influence customer decisions in choosing pension financing at PT Bank Syariah Mandiri Branch Office Bojonegoro Sumberrejo are product quality (X1), service quality (X2), price (X3), emotional (X4), convenience ( X5), promotions (X8) and costs (X9). While simultaneously product quality (X1), service quality (X2), price (X3), emotional (X4), convenience (X5), personal experience (X6), other people's experiences (X7), promotion (X8) and costs ( X9) affects the customer's decision to take pension financing at PT Bank Syariah Mandiri Branch Office Bojonegoro Sumberrejo. The nine factors influence the customer's decision in choosing pension financing by only 66.9 percent, while the remaining 33.1 percent is influenced by other factors. Of the various factors that influence customer decisions in choosing pension financing at PT Bank Syariah Mandiri Branch Office Bojonegoro Sumberrejo, the most significant influence is the price factor (X3).Â Keywords: Pension financing, customer decisions, multiple linear regression analysis